Seismic fragility assessment of a pipe rack structure in a petrochemical complex by incremental dynamic analysis - Jayarajan, P. (Journal of Structural Engineering, 2024)
A typical petrochemical complex consists of various components of different complexities such as structures of variousproportions, critical piping, tanks and massive compressors. The consequences of a seismic event in a process plant issevere compared to conventional civil structures considering that damage to even a single component would result inrelease of toxic gases and lead to an interruption in the production causing economical losses and threat to society andenvironment. Pipe rack structures with the supported piping systems represents an important item in petrochemicalcomplexes, refineries and LNG plants as they run in kilometres of length connecting various process units in thecomplex. The seismic hazard posed by such structures is evident in that they carry piping systems with hazardousfluids and support other critical equipments such as air coolers and exchangers. The paper presents the seismic fragilityassessment for a typical steel pipe-rack structure adapted from a petrochemical complex built in a region of moderateseismicity. Pipe rack structure is first verified for its capacity as per the European codes. The Incremental DynamicAnalysis (IDA) is then performed to obtain an insight into the dynamic response of the structural system in both thetransverse and longitudinal directions. The fragility curves developed for different performance levels based on theIDA data are used for the seismic assessment.